Complete blood count to evaluate major depressive disorder and/or generalized anxiety disorder: A case-control study - Almansour , Abdulelah; Aljubran , Hussain J.; Bamalan , Omar; Abuzaid , Abdullah; AlSharit, Mohammed; Alanazi , Faris; Holdar , Mohammad; AlHarkan , Khalid; Shafey , Marwa (Acta Biomedica Atenei Parmensis, 2024)
Purpose: The aim of this study was to evaluate the clinical diagnostic significance and ratios of complete blood count parameters in patients diagnosed with either or both disorders.Patients and methods: This case-control study included 153 drug-naive patients who were diagnosed with either or both disorders and a matched control group comprised of 163 healthy individuals. The complete blood count parameters with their differentials were calculated and analyzed for all the patients. Moreover, logistic regression analysis was performed using binary logistic analysis.Results: The cases showed a relatively higher basophil count (0.05 ± 0.09, P = 0.013) and basophil percentage (0.98 ± 1.21, P = 0.019) but a significantly lower lymphocyte count (2.17 ± 0.64, P = 0.035), eosinophil count (0.13 ± 0.14, P = 0.003), and eosinophil percentage (2.1 ± 1.82, P = 0.016). In addition, the odds of being a case is lower with a high lymphocyte count (OR = 0.69; P = 0.04), higher with a high basophil count (OR = 203.91; P = 0.01) and after adjusted logistic regression analysis, odds of being a case was lower with a higher red cell distribution width (odds ratio = 0.63; P < 0.001).Conclusion: Several parameters were significantly associated with both major depressive and generalized anxiety disorders. However, larger, multicenter, prospective studies are needed to increase the representation of the data as well as to generalize the results.